Gingival crevicular fluid response to protocols of non-surgical periodontal therapy: A longitudinal evaluation - Vanessa Rossi; Rachel Romagna; Patricia Daniela Melchiors Angst; Sabrina Carvalho Gomes (Wolters Kluwer Medknow Publications, 2019)
Context and Aim: Gingival crevicular fluid (GCF) volume reflects the level of periodontal inflammation. This secondary analysis aimed to evaluate the GCF volume in patients submitted to non-surgical periodontal therapies under a split-mouth design. Materials and Methods: GCF volume of 25 participants (47.24 ± 6.47 years) with moderate-to-severe chronic periodontitis was collected at Days 0, 30, 60, 90, 120, 270, and 450. The participants were submitted to three different non-surgical therapies randomly assigned per quadrant [GI: supragingival control (Supra) as only intervention (one quadrant); GII: Supra plus scaling and root planing (SRP) on Day 0 (two quadrants); GIII: Supra on Day 0 and SRP 30 days later (one quadrant)]. During treatment (0-60 days) and maintenance (90-450 days) participants were submitted to supragingival plaque control reinforcements. GCF volumes were analyzed after logarithmic transformation (log10) and linear models were used for intra- and inter-group comparisons, considering the data dependence. Results: Baseline GCF volumes were similar between groups (GI: 0.39 ± 0.22 μl; GII: 0.42 ± 0.26 μl; GIII: 0.41 ± 0.14 μl;P > 0.05). At Day 60, GCF volumes were significantly reduced (GI: 0.20 ± 0.13 μl; GII: 0.18 ± 0.11 μl; GIII: 0.22 ± 0.13 μl; P < 0.001), without inter-groups differences. These results were maintained along maintenance period (P > 0.05). Even in sites bleeding on probing (BOP) + the means of GCF volume did not differ between groups (P > 0.05). Conclusions: All therapies determined reductions on the GCF volume along time. Supragingival plaque control modulated the subgingival area during the study, reinforcing the importance of this control over the subgingival inflammatory response.